Kebijakan industrial(isasi) dan kontinyuitas konflik industrial pasca krisis ekonomi 1997/1998 - Rochadi, Sigit (Masyarakat, Kebudayaan dan Politik, 2014)
This article examines the relations between industrial policy and industrial conflict in Indonesia pos the 1997 economic crisis. The method uses is descriptive analysis. This research founded that the country's industrial policy was influenced by strong nationalism sentiment of both indigenous and industrialism. This study shows that a prolonged conflict was also influenced by a narrow industry policy. The data was analyzed by descriptive method using critical interpretation; secondary data analysis was conducted by comparing years, business scope, and influencing parties (government, businessman, and labour). The policy did not provide opportunity to strengthen labour, therefore, the issues they echoed was not about technological development or job opportunities, but concerned more about wages or overtime work pay. A successful industrial structural development was not only useful to strengthen national economy, the more important fact is the empowerment of labout through good leadership and democracy.